Pola Produksi Telur Puyuh yang Diberi Ransum Disuplementasi Betain dan Metionin - Ratriyanto, Adi (Universitas Sebelas Maret, 2018)
This study investigated the egg production pattern at the onset of lay until peak production in Japanese quails (Coturnix coturnix japonica) fed diet supplemented with betaine and methionine. Three hundred laying quails were randomly allocated to three groups of supplementations with 5 replicates of 20 quails. The three groups of treatments included basal diet (Control) or basal diet supplemented with 1.2 g betaine and 1.2 g methionine per kg diet. During onset of lay until 50% egg production (6 to 9 weeks of age), all groups were fed a basal diet, while the supplements were applied after 9 weeks. The egg production data were analyzed with analysis of variance and followed by Duncan’s test for significant results. During week 6 to 9, all groups of quails generated similar egg production since they received the basal diet. On the later phase, supplementation of betaine and methionine enhanced average weekly egg production (P<0.05) starting from week 10 compared with those without supplementation. The egg production curves indicated that production rapidly reached 60% soon after the onset of lay. Then, egg production rose sharply and reached the peaks of more than 80%, indicating good egg production patterns. Supplementation of betaine and methionine enhanced the average overall and peak production (P<0.01) without affecting the age at peak production. In addition, there were positive correlations between average of overall production and peak production of all treatments. It can be concluded that supplementation of betaine and methionine enhanced egg production in quails.